Erythrocyte Index–Based Morphological Distribution of Anemia in Patients with Chronic Kidney Disease Undergoing Hemodialysis - Clarissa Anastasya; Elpiani Br Depari; Bagas Prasetyo; Tabita Syahara (Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Anemia is a common complication of chronic kidney disease (CKD), mainly caused by erythropoietin deficiency, although factors such as iron deficiency, chronic inflammation, blood loss, and nutritional disorders may also contribute. Erythrocyte indices, including mean corpuscular volume (MCV) and mean corpuscular hemoglobin concentration (MCHC), are useful for evaluating erythrocyte morphology and identifying potential causes of anemia. Objective: To describe the distribution of anemia morphology based on erythrocyte indices in CKD patients undergoing hemodialysis. Methods: This analytical observational study with a cross-sectional design was conducted at the Hemodialysis Unit of Grandmed Hospital, Lubuk Pakam, from January to March 2026. Data were obtained from complete blood count results in patients’ medical records. Hemoglobin, MCV, and MCHC were analyzed, and anemia morphology was classified based on erythrocyte index